Isotopic Discrimination Factors (Delta C-13 and Delta N-15) between Tissues and Diet of the Broad-Snouted Caiman (Caiman latirostris) - Marques, Thiago S.; Bassetti, Luis A. B.; Lara, Neliton R. F.; Araujo, Marcio S. [UNESP]; Pina, Carlos I.; Camargo, Plinio B.; Verdade, Luciano M. (Soc Study Amphibians Reptiles, 2014)
Natural variation in stable isotope ratios is a useful tool in diet studies. However, the correct interpretation of isotopic data is reliant on proper estimates of discrimination factors. This study aimed to describe the magnitude of the discrimination factors of carbon and nitrogen isotopes between diet and tissues (Delta C-13(tissue-diet) and Delta N-15(tissue-diet)) of the Broad-snouted Caiman (Caiman latirostris) and to verify potential differences between age classes. The isotopic ratios of carbon and nitrogen (delta C-13 and delta N-15) were determined in samples of two tissue types (claw and scute) collected from 18 captive animals and in 15 samples of their diet. The Delta C-13(tissue-diet) was 1.2 +/- 0.1 parts per thousand for claw and 0.9 +/- 0.2 parts per thousand for scutes; the Delta N-15(tissue-diet) was 1.1 +/- 0.1 parts per thousand for claw and 0.8 0.2%0 for scutes. These values were much lower than the values assumed commonly in ecological studies (3-5 parts per thousand), and similar to a previous study with crocodilians. Our results emphasize the need to determine discrimination factors specific to taxa instead of assuming average values derived from the literature.